ARTIFICIAL INTELLIGENCE EFFECTIVENESS IN SKILL ACQUISITION AND WORKFORCE PREPARATION AMONG VOCATIONAL EDUCATION STUDENTS IN UNIVERSITY OF DELTA AGBOR, DELTA STATE (NAU Journal of Technology and Vocational Education, 2025)
The aim of this paper is to examine artificial intelligence effectiveness in skill acquisition and workforce preparation among vocational education students in University of Delta Agbor, Delta State. Population of the study comprises (120) male and female vocational education students. Random sampling technique was used to select 40 male and 80 female vocational education students for the study. Questionnaire was the instrument used for data collection. Data collected was analyzed using mean and standard deviation to answer the research questions. SPSS version 2.5 statistical tool was used for the analysis, while t-test was used to test the null hypotheses at 0.05 level of significance. The findings of the study show that AI-based tools (e.g., chatbots, speech recognition software) have helped learners to improve their spoken communication skills. AI-assisted platforms have improved learners’ ability to analyze and solve practical problems during vocational field work for instance Industrial Tainting (IT) exercise. The study concluded that AI-based tools (e.g., chatbots, speech recognition software) need to be used by vocational education teachers since it helps learners to improve their spoken communication skills, there is needs for vocational students to use AI-assisted platforms to improve learner’s ability, to analyze and solve practical problems during vocational field work. The study recommended that vocational education students should use AI skill to handled duty assigned to them effectively at the workforce preparation and vocational education students should use AI problem solving skill effectively during workforce preparation
Keywords: Artificial intelligence effectiveness; skill acquisition; workforce; preparation; vocational; education; students; universities